Comparative study on turning CI and CGI using silicon nitride cutting tools - Souza, J. V C; Nono, M. C A; Silva, O. M M; Ribeiro, M. V. [UNESP] (Trans Tech Publications, 2008)
There has been a great interest for improving the machining of cast iron materials in the automotive and other industries. Comparative studies for tool used to machine grey cast iron (CI) and compacted graphite iron (CGI) on dry machining were also performed in order to find out why in this case the tool lifetime is not significantly higher. However the machining these materials while considering turning with the traditional high-speed steel and carbide cutting tools present any disadvantages. One of these disadvantages is that all the traditional machining processes involve the cooling fluid to remove the heat generated on workpiece due to friction during cutting. This paper present a new generation of ceramic cutting tool exhibiting improved properties and important advances in machining CI and CGI. The tool performance was analyzed in function of flank wear, temperature and roughness, while can be observed that main effects were found for tool wear, were abrasion to CI and inter-diffusion of constituting elements between tool and CGI, causing crater. However the difference in tool lifetime can be explained by the formation of a MnS layer on the tool surface in the case of grey CI. This layer is missing in the case of CGI.
Keywords: Compacted graphite iron; Dry machining; Gray cast iron; Machining; Si3N4; Cast iron materials; Comparative studies; Cooling fluids; Flank wears; Grey cast irons; Machining processes; Main effects; New generations; SiN; Tool lifetimes; Tool performances; Tool surfaces; Tool wears; Work pieces; Carbides; Ceramic cutting tools; Ceramic tools; Cutting tools; Graphite; Iron; Machine tools; Metal casting; Metal working tools; Nitrides; Powders; Silicon nitride; Turning; Cast iron